Prevalence of alternative AUG and non-AUG translation initiators and their regulatory effects across plants - Li, Ya-Ru; Liu, Ming-Jung (Genome Research, 2020)
Translation initiation is a key step determining protein synthesis. Studies have uncovered a number of alternative translation initiation sites (TISs) in mammalian mRNAs and showed their roles in reshaping the proteome. However, the extent to which alternative TISs affect gene expression across plants remains largely unclear. Here, by profiling initiating ribosome positions, we globally identified in vivo TISs in tomato and Arabidopsis and found thousands of genes with more than one TIS. Of the identified TISs, >19% and >20% were located at unannotated AUG and non-AUG sites, respectively. CUG and ACG were the most frequently observed codons at non-AUG TISs, a phenomenon also found in mammals. In addition, although alternative TISs were usually found in both orthologous genes, the TIS sequences were not conserved, suggesting the conservation of alternative initiation mechanisms but flexibility in using TISs. Unlike upstream AUG TISs, the presence of upstream non-AUG TISs was not correlated with the translational repression of main open reading frames, a pattern observed across plants. Also, the generation of proteins with diverse N-terminal regions through the use of alternative TISs contributes to differential subcellular localization, as mutating alternative TISs resulted in the loss of organelle localization. Our findings uncovered the hidden coding potential of plant genomes and, importantly, the constraint and flexibility of translational initiation mechanisms in the regulation of gene expression across plant species.
10.1101/gr.261834.120